Vat photopolymerization of polymers and polymer composites: Processes and applications - Ans Al Rashid (14777050) (2021)
Synthesis and manufacturing of polymers and their composites have been a topic of interest recently in research and development owing to their wide margin of superiority over traditionally employed industrial materials. Polymer composites provide a higher strengths, easily customizable product properties, flexible manufacturing processes, high resistance to corrosion or erosion, and lower cost. In addition, the additive manufacturing (AM) techniques for polymer composites offer numerous benefits, including higher accuracy, lesser cost, and complexity of fabricated parts. The recent progress in AM processes has paved the way for even a broader range of design flexibilities and materials selection for several industrial sectors, including mechanical, biomedical, filtration, and electrical. However, some challenges remain in additive manufacturing for polymer composites. Vat photopolymerization (VP) processes is an AM technique that provides a benefit of relatively lower cost and higher resolutions; therefore, a comparative review of VP processes for polymers and polymer composites and their applications is presented in this study. This study aims to provide researchers with an updated understanding of the underlying challenges and opportunities. It will also help the reader to systematically reveal the research problems, gaps and future directions related to polymer composite materials and VP processes. Other Information Published in: Additive Manufacturing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.addma.2021.102279